2022
DOI: 10.1097/dcr.0000000000002089
|View full text |Cite
|
Sign up to set email alerts
|

Appendectomy Is Oncologically Equivalent to Right Hemicolectomy for Well-Differentiated T1 Appendiceal Adenocarcinoma

Abstract: BACKGROUND: Right hemicolectomy is recommended for appendiceal adenocarcinoma but may not be needed for early stage disease. OBJECTIVE: This study aimed to determine whether appendectomy offers adequate oncologic outcomes for T1 appendiceal adenocarcinoma from a national cohort of patients. DESIGN: Patients with T1 appendiceal adenocarcinoma (mucinous and nonmucinous histology) treated with either a right hemicolectomy or appendectomy between 2004 and 2016 were retrieved. Multivariate Cox regression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…However, data suggest that for MAC with peritoneal seeding and low-risk ANOS (T1, low grade, no lymphovascular invasion) there is no survival advantage for including right hemicolectomy over appendicectomy or partial colectomy. 38 , 40 , 41 Our institution has a selective strategy for right hemicolectomy based on tumour grade, radiological findings and patient factors. This is appropriate, given the 21% rate of lymph node involvement in our current cohort is consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…However, data suggest that for MAC with peritoneal seeding and low-risk ANOS (T1, low grade, no lymphovascular invasion) there is no survival advantage for including right hemicolectomy over appendicectomy or partial colectomy. 38 , 40 , 41 Our institution has a selective strategy for right hemicolectomy based on tumour grade, radiological findings and patient factors. This is appropriate, given the 21% rate of lymph node involvement in our current cohort is consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Primary adenocarcinoma of the appendix is a rarely diagnosed malignancy, accounting for less than 6% of neoplastic lesions the appendix and less than 0.5% of all gastrointestinal malignancies. Like other appendicular neoplasms, they are most often an incidental finding after appendectomy (13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…It is often associated with synchronous and metachronous colorectal or extraintestinal cancer. According to the literature, surgical treatment is right hemicolectomy as a primary procedure in case of preoperative or intraoperative diagnosis or as a secondary procedure, two to three weeks after appendectomy, when microscopic examination of the preparation reveals the presence of adenocarcinoma (12,16).…”
Section: Discussionmentioning
confidence: 99%
“…1 However, not all NMACAs are created equal. 2 In this timely study, Straker et al 3 used the National Cancer Database (NCDB) to identify a low-risk group of NMACAs for which less extensive surgical resection (i.e., appendectomy/partial colectomy [A/PC]) would be appropriate. They found that patients who had T1 tumors with good to moderate differentiation and no lymphovascular invasion (LVI) had a low risk of LN metastasis (1.8 %).…”
mentioning
confidence: 99%
“…The same has been observed for well-differentiated appendiceal neuroendocrine tumors, and most recently, for T1 welldifferentiated appendiceal adenocarcinomas, which require only a simple appendectomy. In the recent study, AlMasri et al 2 used the NCDB to examine the outcomes for patients who underwent appendectomy versus right colectomy for T1 (both mucinous and non-mucinous) appendix adenocarcinoma. They found that the OS was better when a right colectomy was performed for moderately or poorly differentiated tumors but not for well-differentiated tumors, similar to the findings of this study.…”
mentioning
confidence: 99%